2020
DOI: 10.18231/2394-5478.2018.0093
|View full text |Cite
|
Sign up to set email alerts
|

Exiguobacterium aurantiacum virulent pigment producing a novel pathogenic bacteria associated with cases of corneal ulcers

Abstract: Blindness is a major public health problem in most developing countries. Corneal ulcer (Keratitis) is a major cause of blindness throughout the world. About 10% cases of blindness are due to corneal ulcer. "Corneal ulcer means loss of corneal substances as a result of infection and formation of raw, excavated area." Bacterial keratitis is an acute or chronic, transient or recurrent infection of the cornea with varying predilection for anatomical and topographical parts of the cornea like marginal or central. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The present study utilized the pigment extraction technique mentioned in Jain and Kamble's [16] and Shatila et al's [17] studies.…”
Section: Pigment Extraction and Its Assessment As A Virulent Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The present study utilized the pigment extraction technique mentioned in Jain and Kamble's [16] and Shatila et al's [17] studies.…”
Section: Pigment Extraction and Its Assessment As A Virulent Factormentioning
confidence: 99%
“…The scavenging activity assay was carried out using methods by Jain and Kamble [16], Awah et al [18], Parul et al [19], and Iheanyichukwu et al [20]. The chemicals used were sodium nitroprusside (10 mM), methanol and Griess reagent (1% sulfanilamide in 5% phosphoric acid and 0.1% naphthyl ethylenediamine dihydrochloride).…”
Section: Nitric Oxide (No) Scavenging Activity Assaymentioning
confidence: 99%
“… Pitt et al (2007) determined susceptibility of E. aurantiacum to all tested antimicrobial drugs, as we did in our study, while Jain with associates (2018) and Chen with collaborators (2017) determined the susceptibility of the bacteria to penicillin, meropenem, gentamicin, ciprofloxacin and rifampicin, and their resistance to tetracycline, erythromycin, clindamycin. The susceptibility to vancomycin was railed in these two studies; the bacteria were sensitive according to Chen et al (2017) and resistant in the publication of Jain and Kamble (2018) . It has been shown that environmental bacteria are involved in the horizontal flow of resistance genes.…”
mentioning
confidence: 99%
“…They form orange-yellow pigmented colonies on blood agar ( Takemura et al 2009 ). E. aurantiacum has been very rarely reported to cause infections in humans worldwide, such as bacteremia in the UK, corneal ulcers in India, and pneumonia in China ( Pitt et al 2007 ; Chen et al 2017 ; Jain and Kamble 2018 ), however, in most works, the origin of the infection is still unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation